1999
DOI: 10.1063/1.873741
|View full text |Cite
|
Sign up to set email alerts
|

Bäcklund transformations, a simple transformation and exact solutions for dust-acoustic solitary waves in dusty plasma consisting of cold dust particles and two-temperature isothermal ions

Abstract: Dusty plasma with inertial dust fluid and two-temperature ions admits both compressive and rarefactive solitary waves. The Korteweg-de Vries equations (KdV-type equations) with cubic nonlinearity at the critical density of low-temperature isothermal ions are considered to discuss properties of dust-acoustic solitary waves. In the vicinity of the critical density of low-temperature ions, a KdV-type equation with mixed nonlinearity is discussed. The method of characteristics is used and the Bäcklund transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Their dynamics have been studied in a series of papers, one of which gives growth rates of instabilities found numerically. 25) In more realistic situation in which the electrons are non-isothermal, Munro and Parkes 15) showed that, with an appropriate modified form of electron number density proposed by Schamel,21) a reductive perturbation procedure leads to a modified form of the modified ZK equation (20).…”
Section: The Periodic Wave Solutions Of the (3 þ 1)-dimensional Modifmentioning
confidence: 98%
See 1 more Smart Citation
“…Their dynamics have been studied in a series of papers, one of which gives growth rates of instabilities found numerically. 25) In more realistic situation in which the electrons are non-isothermal, Munro and Parkes 15) showed that, with an appropriate modified form of electron number density proposed by Schamel,21) a reductive perturbation procedure leads to a modified form of the modified ZK equation (20).…”
Section: The Periodic Wave Solutions Of the (3 þ 1)-dimensional Modifmentioning
confidence: 98%
“…Specific results for dusty plasmas include the possibility that dust acoustic solitary waves admit both compressive and rarefactive solutions. 19,20) However, the KdV equation is considered a spatially one dimensional model. An extensive research work has been done in developing higher dimensional models.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high-order nonlinear terms must be taken into account in some complicated situations like at the critical density or in the vicinity of the critical velocity [6][7][8]. The modified KdV (mKdV)-typed equation, on the other hand, has recently been discovered, e.g., to model the dust-ion-acoustic waves in such cosmic environments as those in the supernova shells and Saturn's F-ring [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Gardner equation has been investigated in detail and can be used to model such physical situations as the dust-acoustic solitary waves in dusty plasmas [6], internal solitary waves in stable, stratified shear flows in ocean and atmosphere [15], ion acoustic waves in plasmas with a negative ion [16], interfacial solitary waves over slowly varying topographies [17] and wave motion in a nonlinear elastic structural element with large deflection [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation